Project-Based Learning (PBL) as an Experiential Pedagogical Methodology in Engineering Education: A Review of the Literature - Silvia Lavado-Anguera; Paloma-Julia V; María-José (MDPI AG, 2024)
This systematic literature review explores how the implementation of project-based-learning (PBL) as an experiential pedagogical methodology in engineering education contributes to the development of real-world skills among students. The methodology applied was the PRISMA protocol with searches in two databases in a 24 year timeframe. The research reviewed 54 pieces to explore the contribution of PBL to seven pillars of a holistic pedagogical model comprising the following categories: technology, an integrated curriculum, an international focus, sustainability, a multidisciplinary focus, simulation, and professional environments. Varied PBL developments across these pillars reveal challenges, including aligning with real-world complexities and promoting interdisciplinary integration. Despite obstacles, PBL in engineering shows promise for enhancing students' skills and channeling the added value of a holistic pedagogical model, despite significant differences in the number of experiences associated with each category. Limitations include restricted article access, emphasizing the need for open science promotion.